Profil pasien COVID-19 rawat inap di Rumah Sakit Ari Canti, Gianyar, Bali, Indonesia - Ni Putu Nita Wiryandari; Ketut Suardamana (Intisari Sains Medis, 2022)
Background: Since March 2020, Coronavirus Disease 2019 (COVID-19) has been declared a pandemic. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) underwent genetic evolution and changes in the nature of the virus, clinical manifestations, and response to treatment. This study aims to determine the profile of hospitalized COVID-19 patients at  Ari Canti Hospital (RSAC), one of the COVID-19 referral hospitals in Gianyar, Bali. Methods: The design was a descriptive cross-sectional retrospective study, using the medical records of confirmed COVID-19 by Real Time Polymerase Chain Reaction (RT-PCR) patients selected by a simple random sampling technique. Results: From 290 samples, the majority of COVID-19 patients treated at RSAC were 60.7% male, in the age range of 50-59 years 26.5%, with severe symptoms 45.8% and recovered 83.4%. The dominant symptoms were fever 85.2%, cough 80%, and shortness of breath 60%. The most common comorbidities were >1 comorbidity, hypertension, and diabetes mellitus. Hematological examination at the first time of hospitalization showed leukopenia (4.8%), lymphopenia (14.5%), thrombocytopenia (12.8%),  and anemia (21.7%). The results also showed an increase in Neutrophil to Lymphocyte ratio (NLR) (31.4%), Platelet to lymphocyte ratio (PLR) (11.7%), Red Cell Distribution Width (RDW) (40.7%), D-Dimer  (73.4% ) dan High sensivity C-Reactive Protein (Hs-CRP)  (66.6%). Most showed bilateral infiltrates on chest x-ray. The most common treatment for COVID-19 at RSAC uses antiviral remdesivir (77.9%), quinolone antibiotics (73.4%), and Low Molecular Weight Heparin (LMWH) (53.4%).  A total of 56.6% of patients received corticosteroid therapy. Conclusion: Patients hospitalized at RSAC mostly showed severe symptoms and recovered. The treament folowing the standard of inpatient treatment for COVID-19 patients.   Latar belakang: Sejak Maret 2020, Coronavirus Disease 2019 (COVID 19) dinyatakan sebagai pandemi. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) mengalami evolusi genetik dan perubahan sifat virus, manifestasi klinis serta respon pengobatan. Penelitian ini bertujuan untuk mengetahui profil pasien COVID-19 yang dirawat di Rumah Sakit Ari Canti (RSAC), salah satu rumah sakit rujukan COVID-19 di Gianyar, Bali Metode: Rancangan penelitian ini adalah cross-sectional deskriptif retrospektif, menggunakan rekam medis pasien terkonfirmasi COVID-19 dengan Real Time Polymerase Chain Reaction (RT-PCR) sejak Juli 2020 - Maret 2022 yang dipilih dengan teknik simple random sampling. Hasil: Dari 290 sampel, mayoritas pasien COVID-19 yang dirawat di RSAC adalah laki-laki 60.7%, berada pada rentang usia 50-59 tahun 26.5%, dengan gejala berat 45.8% dan sembuh 83.4%. Gejala didominasi demam 85.2%, batuk 80%, dan sesak 60%. Komorbid tersering yaitu >1 komorbid, hipertensi, dan diabetes melitus. Gambaran hematologi menunjukkan leukopenia (4.8%), limfopenia (14.5%), trombositopenia (12.8%), dan  anemia (21.7%). Hasil juga menunjukkan peningkatan Neutrophil to Lymphocyte ratio (NLR) (31.4%), Platelet to lymphocyte ratio (PLR) (11.7%), Red Cell Distribution Width (RDW) (40.7%), D-Dimer (73.4% ) dan High sensivity C-Reactive Protein (Hs-CRP) (66.6%). Sebagian besar menunjukkan infiltrat bilateral pada x-ray thorax. Tatalaksana COVID-19 di RSAC tersering menggunakan antivirus remdesivir (77.9%), antibiotik golongan kuinolon (73.4%), dan antikoagulan Low Molecule Weight Heparin (LMWH) (53.4%). Sebanyak 56.6 % pasien mendapat terapi kortikosteroid. Kesimpulan: Pasien COVID-19 yang dirawat di RSAC sebagian besar menunjukkan gejala berat dan sembuh. Terapi yang diberikan mengikuti standar terapi rawat inap pasien COVID-19.